2022
DOI: 10.1016/j.cresp.2021.100028
|View full text |Cite
|
Sign up to set email alerts
|

Concern with COVID-19 pandemic threat and attitudes towards immigrants: The mediating effect of the desire for tightness

Abstract: Tightening social norms is thought to be adaptive for dealing with collective threat yet it may have negative consequences for increasing prejudice. The present research investigated the role of desire for cultural tightness, triggered by the COVID-19 pandemic, in increasing negative attitudes towards immigrants. We used participant-level data from 41 countries ( N = 55,015) collected as part of the PsyCorona project, a cross-national longitudinal study on responses to COVID-19. Our pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…In the present study, we focus on whether people’s desired tightness may mediate the relationship between the perceived COVID-19 threat and emotional reactions to noncompliance with COVID-19 health-protective behaviors; we expect that the perceived COVID-19 threat may increase people’s desire for restrictions and sanctions where they reside, consistent with previous findings [ 7 , 11 , 12 ]; given that age-related differences were found in the perceived cost of COVID-19 infection and actual health risk [ 23 , 31 ], we also expect that participants’ age will moderate this relationship. Although research on COVID-19 has been very common since the start of the pandemic, to our knowledge this is the first attempt to study how socio-psychological variables can predict reactions to pandemic-specific non-compliance.…”
Section: The Present Researchsupporting
confidence: 79%
See 4 more Smart Citations
“…In the present study, we focus on whether people’s desired tightness may mediate the relationship between the perceived COVID-19 threat and emotional reactions to noncompliance with COVID-19 health-protective behaviors; we expect that the perceived COVID-19 threat may increase people’s desire for restrictions and sanctions where they reside, consistent with previous findings [ 7 , 11 , 12 ]; given that age-related differences were found in the perceived cost of COVID-19 infection and actual health risk [ 23 , 31 ], we also expect that participants’ age will moderate this relationship. Although research on COVID-19 has been very common since the start of the pandemic, to our knowledge this is the first attempt to study how socio-psychological variables can predict reactions to pandemic-specific non-compliance.…”
Section: The Present Researchsupporting
confidence: 79%
“…As mentioned, when societies face societal threats, tight rules and punishments for people who deviate from norms may help them to coordinate in order to survive [ 8 , 10 ]. Likewise, correlational and experimental findings [ 7 , 11 , 12 ] showed that threat also affects the desire that rules be stricter in the face of threat. This finding has been consistently shown by as a number of studies.…”
Section: Threat Tightness and Implicationsmentioning
confidence: 99%
See 3 more Smart Citations